Comment on 'effects of acetaminophen on risk taking'. Issue 5 (25th February 2021) - Ross, Jennifer A; Holstege, Christopher P
Abstract: The article by Keaveney et al . entitled 'Effects of acetaminophen on risk taking' was published in July of 2020 and concluded that using acetaminophen increased risk-taking behaviors, potentially by reducing perceived risk. We believe that there is not enough data to support the generalization of this association and feel that the conclusions were presented without acknowledgement of the limitations of this study. Media articles often further dramatized these findings, presenting the potential correlation between acetaminophen and risk taking as fact. It is unfair to readers to sensationalize the associations seen in controlled experiments in an attempt to generalize the study's findings. As scientists, we need to assure that the discussions and conclusions presented in publications appropriately highlight the limitations of studies. We must also work to assure that the public does not sensationalize preliminary and limited research results.